Fathering Practices in Sweden During the COVID-19: Experiences of Syrian Refugee Fathers - Wissö, Therése; Bäck-Wiklund, Margareta (Frontiers in Sociology, 2021)
This article explores fathering practices among Syrian refugee families in Sweden. Syrian refugees provide an example of people who migrated because of a single major event: the war in Syria. The article examines the impact of the COVID-19 pandemic on fathering practices. The Swedish COVID-19 strategy differed from those adopted in many other countries. Lockdowns were minimal and were not stringently enforced, based on the assumption that individuals would trust the authorities and would take personal responsibility for complying with their guidelines and recommendations. Previous research suggests that migrants and other vulnerable groups were not always well informed about the public policies introduced prior to and during the pandemic. The article draws on empirical data from a wider research project on the family lives of Syrian migrants in Sweden. The authors present their findings from an analysis of eleven ethnographically informed semi-structured interviews, carried out before and during the pandemic, with married fathers who had been living in Sweden for several years. In this article, they focus on three cases representing fathers with varied educational backgrounds and employment histories. These families had in common what are considered by Swedish standards to be overcrowded living conditions; they were forced to accept close family proximity, both physically and emotionally, as they no longer had the supportive networks they were used to in Syria. The three fathers were found to rely more heavily on information provided by the people with whom they were in contact in Sweden than on policies and recommendations from the authorities. These findings confirmed that the previous experiences among refugees of shifting policies regarding migration and integration had lowered their trust in government. They had learnt that they needed to rely on mutual dependency not only between spouses, but also between parents and children.